2019
DOI: 10.3390/ijms20163997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Layer Charge Density on Hydration Properties of Montmorillonite: Molecular Dynamics Simulation and Experimental Study

Abstract: Four kinds of Ca-montmorillonite with different layer charge density were used to study the effect of charge density on their hydration properties by molecular dynamics simulation and experiments. The research results of Z-density distribution of water molecules, Hw (hydrogen in water molecules), and Ca in the interlayer of montmorillonite show that the hydration properties of montmorillonite are closely related to its layer charge density. If the charge density is low, the water molecules in the interlayers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Therefore, the relative concentration of H 2 O decreases with the increase of layer charge. This conclusion fits well with our previous study [29].…”
Section: Z-axis Concentration Profiles Of H 2 Osupporting
confidence: 94%
See 3 more Smart Citations
“…Therefore, the relative concentration of H 2 O decreases with the increase of layer charge. This conclusion fits well with our previous study [29].…”
Section: Z-axis Concentration Profiles Of H 2 Osupporting
confidence: 94%
“…Regarding the impact of crystal structure on the hydration properties of MT, Qiu et al studied the effect of charge density on the hydration properties of Ca-MT by combining molecular dynamics simulation and experimental methods. We found that the polarity of Ca-MT sheets was strengthened when the charge density increased, so the interlayer particles were more likely to be drawn to tetrahedral surfaces [29], Shen et al also drew a similar conclusion [30]. Wungu et al compared the effect of isomorphic substitution or a non-isomorphic substitution on the geometric structure and electronic properties of MT using DFT calculations.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…According to the simulation results, we can further prove the rationality of conclusions and predict the experimental results. [2,21,22] Up to now, molecular simulation methods have been successfully used in the study of MMT and achieved many amazing research results, [14,23,24] such as the distribution and hydration characteristics of inorganic cation in MMT interlayers, [25][26][27][28] the distribution and kinetic characteristics of various kinds of atoms in organic modifiers and the arrangement of the organic modifiers in MMT interlayers. [29][30][31][32] At present, the research on organic MMT by molecular simulation mainly focuses on the effect of carbon chain length and the amount of modifier on the structure of organic MMT and the arrangement of organic modifier in MMT interlayers.…”
Section: Introductionmentioning
confidence: 99%